Performance Analysis Of Acceleration Sensor For Movement Detection In Vehicle Security System - Mohamed Kassim, Anuar; Awangku Jaya, Awangku Khairul Ridzwan; Azahar, Arman Hadi; Jaafar, Hazriq Izzuan; Subramonian, Sivarao; Jafar, Fairul Azni; Mohd Aras, Mohd Shahrieel (Science and Information Organization, 2019)
The vehicle security system is a critical part of an entire car system in order to prevent unauthorized access into the car. As the statistic has shown that the number of cases of the private car being stolen is increasing and the recovery rate is decreasing sharply, it shows that the car security system failed to perform to prevent unauthorized access. Most of the vehicle security system simply consists of a few door-open detection switches, siren, and remote control to protect the car, which appears to be weak against experienced car theft. Therefore, the project is carried out to develop a vehicle security system that can measure the dynamic acceleration inside the vehicle using the ADXL345 accelerometer and locate the coordinate of the vehicle by using U-Blox Neo-6M GPS receiver. In order to evaluate the performance of the proposed vehicle security system, the experiment to determine the most suitable position among the four places inside a car to place the device was conducted. Then, the performance analysis of the GPS receiver for accurate tracking also was done. The results showed that the most suitable position to place the device is inside the center of the car dashboard and the GPS receiver has a mean cold start-up time of 5 minutes 47 seconds and hot start-up time of 11.72 seconds, with a standard deviation of 0.000003706° in latitude and 0.000002762° in longitude for position tracking.